Cross-Coupled Line Bandpass Filter Based on Modified Parallel-Coupled Line Structure - Fajri Darwis; Enjel Al Birr Rahayu; Sutrisno Sutrisno; Hanny Madiawati; Taufiqqurrachman Taufiqqurrachman; Arie Setiawan; Erry Dwi Kurniawan; Yusuf Nur Wijayanto (National Research and Innovation Agency, 2022)
This paper presents a study of a narrow bandwidth of the bandpass filter with a cross-coupled line structure. This structure was designed to have a good filter selectivity with the transmission zeros and a simple design. Since the structure has a cross shape, cross-coupling between the resonators consequently occurs. This interferes with the passband of the filter. Optimization in the size of the coupled lines and transmission lines was done to minimize the interference. Rogers RT/duroid 5880 was used as a substrate to fabricate the bandpass filter to verify the proposed design. As a result, the fabricated cross-coupled line bandpass filter has an 80 MHz of 3 dB bandwidth with operating frequency ranges from 2.97 GHz to 3.05 GHz. The bandwidth is reduced by 20 % from the specification.It shows that the cross-coupled line structure can yield a narrow bandwidth. Based on the 3 dB bandwidth, the center frequency is shifted 0.33 % above the specification. Meanwhile, the return loss and insertion loss of the proposed bandpass filter successfully comply with the required specifications. In conclusion, the proposed bandpass filter can be applied to S-Band applications that require narrow bandwidth.